The Negotiation of English Teachers’ Identity Representation In EFL Classroom - Irene Rosalina (STAI Nurul Islam Mojokerto, 2021)
This study applies a sociocultural linguistic approach where it examined the representation of English as International language teachers' identity negotiation in their classroom interactions. The important role of the teachers involving their efforts, values ​​, and beliefs preceded this study. Furthermore, the findings in this study indicated that the English teachers negotiate their identity as they still bring out the teaching with the reference to cultural, social, political, and religious constructs. The different ways of the teachers showing their identity infused in their linguistic use in the classroom. Moreover, the religion bounding values and beliefs that the teachers motivated to explore were shown in the connection between the English teaching topic being discussed in class and the religious concept in teaching, which in this case related to the Islamic teachings. The teachers also perceive their identities which can be assembled into four broad areas showing their understanding and the important function of their identity representations in the way of teaching. Lastly, some pedagogical implications were also found from this study.